THE CURRENT STATUS AND STEPS TOWARDS SUSTAINABLE WASTE MANAGEMENT IN THE DEVELOPING COUNTRIES: A CASE STUDY OF PESHAWAR-PAKISTAN - Muhammad Waqas (Universitas Trisakti, 2019)
Aim: This article was meant to review the current status and limitations of treating municipal solid waste (MSW) by the developing countries with a case study from Peshawar-Pakistan. Methodology and Results: The city is divided into 4 towns and used a stratified sampling and survey to inspect MSW management from collection to final disposal. The results show food contributes to 14.3% of the total waste, followed by plastic waste 4%, paper, 2.7%, glass 1.2%, wood 1.1%, and metals/rubber 0.6%. Conclusion, significance, and impact study: About 60% of the wastes at collection points make the air difficult for breathing. There are several treatment options for the sustainable management of MSW, including composting, incineration, gasification, pyrolysis, biological treatment, and recycling. The developed countries had strictly imposed regulations to increase waste recycling and material recovery. In contrast, in the developing countries, the lack of proper legislation, planning, and awareness regarding waste reduction has worsened the MSW related problems. In this article, the essential steps needed in formulating the strategy for sustainable MSW management and assessment in terms of sustainability in the developing countries have been considered.